Prevalence of copycat in Africa textile clusters: the blame game among stakeholders - Asare-Kyire, Lydia; He, Zheng; Essel, Charles Hackman; Junaid, Danish (Journal of Business Economics and Management, 2018)
In this paper we investigate the reasons behind the pirated textiles and try to address the questions of why copycats are rampant on the African textile market, their impact on textile clusters and why it is ineffectively being controlled. Taking Ghana as a sample, this study employed grounded theory methodology to explore the key factors that account for copycat prevalence in African textile industry. This study reveals that economic foundations, political factors and stakeholder interactions in the textile ecosystem have influenced copycat popularity in Africa. More specifically, the blame game among stakeholders with no one accepting responsibility for copycat prevalence gave space for perpetrators of copycat textiles to breed. The study extends the stakeholder and cluster theories particularly within the confines of developing regions, the interplay of actors and how their actions promote or revert the fight against copycats. This article implores governments should proactively lead in collaborative inter-agency actions to fight the copycat menace by repackaging and designing strategies/approaches through the employment and increasing of stakeholder consultations.